Adjuncts to Improve Nasal Reconstruction Results - Gordon, Shayna Lee; Hurst, Eva A. (Facial Plastic Surgery, 2017)
The final cosmetic appearance of nasal reconstruction scars is of paramount importance to both the patient and surgeon. Ideal postreconstruction nasal scars are flat and indistinguishable from surrounding skin. Unfortunately, even with meticulous surgical execution, nasal scars can occasionally be suboptimal. Abnormal fibroblast response can lead to hypertrophic nasal scars, and excessive angiogenesis may lead to telangiectasias or an erythematous scar. Imperfect surgical closure or poor postoperative management can lead to surgical outcomes with step-offs, depressions, suture marks, or dyspigmentation. Aesthetically unacceptable nasal scars can cause pruritus, tenderness, pain, sleep disturbance, and anxiety and depression in postsurgical patients. Fortunately, there are several minimally invasive or noninvasive techniques that allow for enhancement and improvement of cosmetic results with minimal risk and associated downtime. This article provides an overview of adjuncts to improve nasal reconstruction with a focus on techniques to be used in the postoperative period. Armed with an understanding of relevant available therapies, skillful surgeons may drastically improve the final cosmesis and outcome of nasal reconstruction scars.
Keywords: nasal reconstruction; steroid scar injection; resurfacing